Male and female urinary incontinence management - M. I. Kogan (Вестник урологии)
The article summarises the guidelines of the International Continence Society (ICI-7) for the management of male and female urinary incontinence. The author's opinion on the state of the problem from the perspective of its relevance in the field of modern practical urology is expressed.